2009
DOI: 10.1007/s00500-009-0479-0
|View full text |Cite
|
Sign up to set email alerts
|

Online chaotic time series prediction using unbiased composite kernel machine via Cholesky factorization

Abstract: The kernel method has proved to be an effective machine learning tool in many fields. Support vector machines with various kernel functions may have different performances, as the kernels belong to two different types, the local kernels and the global kernels. So the composite kernel, which can bring more stable results and good precision in classification and regression, is an inevitable choice. To reduce the computational complexity of the kernel machine's online modeling, an unbiased least squares support v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The kernel (20) can be easily generalized to the multidimensional version by using the tensor product…”
Section: Construction Of the Multiscale Orthogonalmentioning
confidence: 99%
“…The kernel (20) can be easily generalized to the multidimensional version by using the tensor product…”
Section: Construction Of the Multiscale Orthogonalmentioning
confidence: 99%
“…Recently, researchers found that the prediction precision can be improved by using some combined techniques. These include artificial neural networks combined with fuzzy theory [9,10], the unbiased composite kernel LSSVR [11], and -nearest neighbors with phase space reconstruction [12]. Generally, these methods can obtain better results than traditional individual models, but they are complex, and the parameter selection is affected by personal experience.…”
Section: Introductionmentioning
confidence: 99%